2019
DOI: 10.1029/2018ef001088
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Footprint of Rapid Arctic Change

Abstract: Arctic land ice is melting, sea ice is decreasing, and permafrost is thawing. Changes in these Arctic elements are interconnected, and most interactions accelerate the rate of change. The changes affect infrastructure, economics, and cultures of people inside and outside of the Arctic, including in temperate and tropical regions, through sea level rise, worsening storm and hurricane impacts, and enhanced warming. Coastal communities worldwide are already experiencing more regular flooding, drinking water conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
0
23
0
2
Order By: Relevance
“…The hypothesized opening of Fram Strait between the Nordic Seas and the Arctic at around 17 Ma (Jakobson et al, 2007; Thompson et al, 2010) may have contributed to the MCO by allowing warmer surface waters to enter the Arctic Basin, thereby leading to increased Arctic SSTs and decreased seasonal Arctic sea ice (St. John, 2008). It has been argued that the strong climatic feedback of sea ice reduction in the Arctic (e.g., Moon et al, 2019) might then have led to the global warming observed during the MCO (Jakobsson et al, 2007). However, our evidence suggests that overturning circulation that resulted in the transportation of warm surface water to the Nordic Seas by a NAC‐precursor was actually relatively enhanced as the MCO came to an end, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized opening of Fram Strait between the Nordic Seas and the Arctic at around 17 Ma (Jakobson et al, 2007; Thompson et al, 2010) may have contributed to the MCO by allowing warmer surface waters to enter the Arctic Basin, thereby leading to increased Arctic SSTs and decreased seasonal Arctic sea ice (St. John, 2008). It has been argued that the strong climatic feedback of sea ice reduction in the Arctic (e.g., Moon et al, 2019) might then have led to the global warming observed during the MCO (Jakobsson et al, 2007). However, our evidence suggests that overturning circulation that resulted in the transportation of warm surface water to the Nordic Seas by a NAC‐precursor was actually relatively enhanced as the MCO came to an end, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Arctic is warming twice as fast as other regions [44]. Because a changing Arctic cryosphere has a far-reaching footprint of influence in distant geographies, constructive multilevel adaptive actions are needed [45]. Northern Alaska's communities, in this sense, are laboratories for learning, through which a global audience can glimpse their own future challenges related to collective adaptive action.…”
Section: Study Areamentioning
confidence: 99%
“…Сокращение площади морского льда оказывает прямое воздействие на многие морские и прибрежные виды, находящиеся в зависящих ото льда пищевых цепочках [6,18], ставя некоторые из них на грань выживания. Уменьшение площади морского льда также имеет широкие косвенные последствия, в том числе путем воздействия на температуру и количество осадков на суше [18,20]. Условия открытой воды повышают вероятность выпадения осадков в жидкой фазе, которые могут приводить к образованию ледяной корки на снегу, препятствующей питанию животных.…”
Section: экологические последствия сокращения морского ледяного покроваunclassified